Gambaran Pelaksanaan Sholat pada Pasien Rawat Inap di RS PKU Muhammadiyah Bantul - Widiasari, Vinna; Yuniarti, Falasifah (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Fulfilling spiritual needs, including prayer, is an essential part of holistic care for hospitalized pediatric patients, but its implementation often faces challenges. This study aims to determine the practice of prayer among pediatric patients hospitalized at PKU Muhammadiyah Bantul Hospital. The method used was a qualitative research approach with a single case study approach, with a 5-year-old child and her mother as participants. Data collection was conducted through in-depth interviews using open-ended questions based on Gordon's theory. The results indicate that religion plays a significant role as a source of peace and guidance for patients and their families. Prayer practice during hospitalization tends to decline, influenced by the patient's health condition, lack of habituation, and inadequate family support in assisting children with worship. On the other hand, illness is interpreted as a means of reflection to draw closer to God and cultivate patience. The results of this study conclude that the implementation of religious activities among hospitalized pediatric patients is still suboptimal, necessitating the active involvement of nurses and families in providing support and facilitating the fulfillment of patients' spiritual needs during the treatment process.